FINANCIAL ANALYSIS ON DEVELOPMENT OF COAL LIQUEFACTION PLANT IN INDONESIA USING BROWN COAL LIQUEFACTION (BCL) TECHNOLOGY - MIFTAHUL HUDA; Granit Agustina; NINING S. Ningrum; BUKIN DAULAY (Puslitbang tekMIRA, 2009)
Financial analysis of Mulia coal liquefaction plant has been conducted in the year 2002 and up dated in the year 2007. However, the increase of coal price, currently, has promoted coal companies to export their coal rather than to allocate it as raw material for coal liquefaction. To maintain the stability of coal supply in a liquefaction plant, the use of stranded mining coal as raw material for the plant should be studied. This study was aimed to conduct financial analysis of stranded coal from South Sumatera (Pendopo Coal) and to update the financial analysis of Mulia coal liquefaction. Discounted cash flow was used as the method for the analysis. The result indicates that with the oil price higher than US 70/bbl and coal price below US 25/ton, the Internal Rate of Return (IRR) of Pendopo coal liquefaction plant achieved value higher than 10%. Reducing corporate tax from 30% to 15% in- creased IRR value of approximately 1%. Meanwhile, by enlarging the plant scale from 3,000t/d to 12,000 t/d will increase the IRR value as much as 5%. On the other hand, the IRR of Mulia coal liquefaction plant was less than 9% when the oil price was lower than US 70/bbl and coal price was above US 55/ton.